Respiratory microbiota: addressing clinical questions, informing clinical practice. Issue 1 (17th July 2014) - Rogers, Geraint B; Shaw, Dominick; Marsh, Robyn L; Carroll, Mary P; Serisier, David J; Bruce, Kenneth D
Abstract : Over the last decade, technological advances have revolutionised efforts to understand the role played by microbes in airways disease. With the application of ever more sophisticated techniques, the literature has become increasingly inaccessible to the non-specialist reader, potentially hampering the translation of these gains into improvements in patient care. In this article, we set out the key principles underpinning microbiota research in respiratory contexts and provide practical guidance on how best such studies can be designed, executed and interpreted. We examine how an understanding of the respiratory microbiota both challenges fundamental assumptions and provides novel clinical insights into lung disease, and we set out a number of important targets for ongoing research.